Immune Tolerance Induction (ITI) with a pdFVIII/VWF Concentrate (octanate) in 100 Patients in the Observational ITI (ObsITI) Study - Escuriola Ettingshausen, Carmen; Vdovin, Vladimír; Zozulya, Nadezhda; Svirin, Pavel; Andreeva, Tatiana; Benedik-Dolničar, Majda; Jiménez-Yuste, Victor; Kitanovski, Lidija; Zupancic-Šalek, Silva; Pavlova, Anna; Bátorová, Angelika; Montaño Mejía, Cesar; Abdilova, Gulnara; Knaub, Sigurd; Jansen, Martina; Lowndes, Shannely; Belyanskaya, Larisa; Walter, Olaf; Oldenburg, Johannes; on behalf of the ObsITI Study Group (TH Open, 2022)
Background Immune tolerance induction (ITI) with repeated factor VIII (FVIII) administration is the only strategy proven to eradicate inhibitors. The observational ITI study is evaluating ITI with a range of FVIII products.Methods This subgroup analysis reports prospective interim data for patients treated with a plasma-derived, von Willebrand factor-stabilized FVIII concentrate (pdFVIII/VWF, octanate). Complete success (CS) of ITI required achievement of three criteria: inhibitor titer < 0.6 BU/mL; FVIII recovery ≥ 66%; FVIII half-life ≥6 hours. Partial success (PS) required achievement of two criteria and partial response (PR) one. ITI success was defined as CS or PS. Data were analyzed for patients who achieved CS, had 36 months' observation, or failed ITI.Results One-hundred prospectively enrolled patients were included in the analysis; 91 had poor prognosis factors for ITI success. The mean (standard deviation) daily ITI dose was 116.4 (61.1) IU FVIII/kg in 14 low responders (< 5 BU/mL) and 173.7 (112.0) IU FVIII/kg in 86 high responders (≥ 5 BU/mL). Inhibitor titers < 0.6 BU/mL were achieved in 71% of patients in a median of 4.01 months, accompanied by a 93% reduction in bleeding rate. ITI success was achieved by 70% of patients and 56 of 72 (78%) primary (first-line) ITI patients. PR was achieved by 5 patients; ITI failed in 25 patients. PS and CS were achieved in a median of 5.55 and 11.25 months, respectively.Conclusions ITI with pdFVIII/VWF led to rapid eradication of FVIII inhibitors, normalization of FVIII pharmacokinetics in the majority of patients, and a significant reduction in bleeding rates.
Keywords: factor VIII; von Willebrand factor; FVIII inhibitors; hemophilia A; immune tolerance